Re-examining the impact of globalisation on economic growth: evidence from South America - Muhammad Ariff Azhan Norli; Chia, Yee Ee (Penerbit UMS, 2021)
This study aims to re-examine the relationship between globalisation and economic growth in nine South America countries using the new KOF globalisation index. The new improvement version of globalisation index contains 43 variables compare to only 23 variables in the Dreher (2006) version which is more precisely quantifies the all-encompassing concept of globalisation. The new index of globalisation includes both de facto and de jure measures that would influence economic growth differently in certain countries. The data spanning a 17-year period from 2002-2018. Our baseline pooled Ordinary Least Squares (OLS) regression model finds that globalisation is positively and significantly associated with higher economic growth. This suggests that globalisation improves growth in overall South America countries. Hence, our key findings are supported with a battery of robustness tests, namely Fama MacBeth, quantile regression, and firm fixed effects.